Succeeding Generations : On the Effects of Investments in Children - Haveman, Robert H.; Wolfe, Barbara L. (Book collections on Project MUSE., 1995)
If America's future depends on how well we take care of our children, then current trends point toward a bleak horizon. Teenage suicide and pregnancy rates climbed over the past two decades, while the average SAT score, despite recent improvement, remains at an abysmally low level. Succeeding Generations ascribes the precarious state of America's youth to the increasingly unstable environment in which we as a society and as parents have chosen to raise our children. Authors Robert Haveman and Barbara Wolfe present a meticulous and candid investigation that directly links fractured families, a troubled economy, rising poverty rates, and neighborhood erosion to the impaired ability of many children to lead successful and productive adult lives. Drawn from an extensive two-decade longitudinal survey of American families, Succeeding Generations traces a representative group of America's children from their early years through young adulthood. The book then evaluates the many background factors - family, social, and economic - which are most influential in determining how much education children will obtain, whether they will become teen parents, and how economically active they will be when they reach their twenties. Haveman and Wolfe pinpoint some significant causes of children's later success, emphasizing the importance of parents' education and, despite the apparent loss of time spent with children, the generally positive influence of maternal employment. Haveman and Wolfe also confirm the detrimental effects on children of the very phenomena which have increased over the past two decades: divorce, single parent families, geographic relocation, and neighborhood deterioration. Most alarming is the epidemic of the single greatest deterrent to children's future success - poverty. Today twenty percent of all American children - forty percent among minorities - grow up in poor families, more than in other Western developed countries. Succeeding Generations demonstrates how the future of America's children has been placed at risk by social and economic conditions which, if perpetuated, are almost certain to foster an intergenerational chain of failure. Arguing the need for intervention, Haveman and Wolfe supplement their research with a comprehensive review of the many debates among economists, sociologists, developmental psychologists, and other experts on how best to improve the lot of America's children. Succeeding Generations is an important assessment of the disadvantages facing today's youth, and a cornerstone upon which to strengthen the investments we make in our children.